Carbon Tax : Potential For State Revenue And Potential For Carbon Emission Reduction In Indonesia - Al Maliki, Muhamad Aburizal; Devano, Sony; Muhlisin, Arif (UNIVED Press, 2026)
This study aims to analyze the potential impact of carbon tax implementation on state revenue and carbon emission reduction in Indonesia. Using a mixed-methods approach that combines both qualitative and quantitative methods, data were collected through interviews and document analysis. The results indicate that implementing a carbon tax in Indonesia holds significant potential for increasing state revenue. By applying the calculation formula namely Revenue = Carbon Emissions × Tax Rate, the estimated state revenue would reach approximately IDR 123.86 trillion for the period of 2018–2022, assuming a carbon tax rate of IDR 30,000 per ton CO₂e is applied nationally. This finding suggests that carbon tax can function not only as an environmental control instrument but also as a strategic alternative source of state financing in the transition toward a green economy. Additionally, the carbon tax has the potential to reduce carbon emissions. Based on the OECD (2022) study, each €10/ton CO₂e increase results in a 1.5% decrease in emissions, implying an emission-price elasticity (dE/dP) of -0.15. If Indonesia implements a tax rate equivalent to €30/ton CO₂e, the theoretical emission reduction could reach 4.5%. This level of elasticity demonstrates that a carbon tax policy could serve as an effective instrument for gradual emission reduction, particularly when expanded to major sectors such as energy, transportation, and land-use change.